Modelo estratégico para empresas familiares: enfocado en la profesionalización y planeación estratégica como factores de incidencia en la continuidad y crecimiento de las mismas. (2020)
The fundamental purpose of this research is outlined within the framework of generating a strategic planning model in this type of company, from the identification of the following study categories: family business, professionalization, generational change, succession, business continuity and strategic planning. The categories of study in the present investigation arise from the inquiry at first about the thoughts taught by different authors who described key concepts, which are fundamental bases for the construction of a double entry model. After this, an exhaustive analysis is carried out on the study categories proposed which shape the model. Which obtains a multi-criteria approach, in addition to it having factors such as: Professionalization, succession, generational change and business continuity, and guidelines such as: management (decision-making), vocation of continuity and majority ownership. The result of this category combination is the development of strategic tips that can change the direction of an organization to a certain extent. Therefore, this research aims to establish a model in strategic matters that they use as a business management tool, as mentioned by Armijo (2009), as a support for effective decision-making by companies.